HUBUNGAN PENERAPAN PRINSIP PEDOMAN GIZI SEIMBANG DENGAN STATUS GIZI MAHASISWA S1 DEPARTEMEN ILMU GIZI FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO SEMARANG - Tessanika Juniar Pratami; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Student as preadult still requires the fulfillment of nutrients to support the activities during the course. But many students were the nutritional requirements have not been met thus causing a problem of nutrition, such as shortages and excess nutrients, can be prevented by the understanding and practice in accordance with the principles and guidelines for balanced nutrition. This research aims to see the correlation between attitudes grateful for the diversity of food, habit of eating a varied, hygiene lifestyle, physical activity, sufficiency level of energy protein and nutritional status of students. This research used a cross sectional to measure the independent and dependent variables at the same time. The population is all the Nutrition Public Health students Diponegoro University. Samples numbered 36 people using total sampling technique. Analysis of data using statistical test of Rank Spearman with a significance of 5% (0,05). The results showed there were 18 students who have a normal nutritional status, 23 of 36 students agreed to the attitude of grateful for the diversity of food, 18 students have the habit of eating were poor, 18 students have good hygiene life, 18 students have moderate physical activity, 26 students have under RDA of energy, and there were 25 students have upper RDA of protein. This study showed no association of food diversity grateful attitude (p = 0,163; r = -0,237), the habit of eating a variety of foods (p = 0,81; r = 0,638), a clean lifestyle (p = 0,203; r = 0,235), physical activity (p = 0,992; r = -0,002), and there is a correlation energy sufficiency level (p = 0,005; r = -0,460), protein sufficiency level (p = 0,001; r = -0,549) on the nutritional status of students. Suggestion of this research students need to pay attention to their weight and improve their nutritional status by applying the principles and guidelines for balanced nutrition.